Influence of ionic liquid in modified paste carbon electrode to voltametric signals of 2,4,6-trinitrotoluene (TNT) in phosphate buffer solution - Vinh Hanh, Le Thi; Anh, Nguyen Hoang; Hai Yen, Pham Thi; Hung, Le Quoc; Tuan, Nguyen Thanh; Thu Ha, Vu Thi (Vietnam Journal of Chemistry, 2014)
Fabrication of ionic liquid modified paste-carbon-electrodes (ILPCEs) and its application in measuring electrochemical properties of 2,4,6-trinitrotoluene (TNT) were investigated in this study. The modified electrodes were prepared ​​by carbon powder (Cp) with ionic liquid 1-Butyl-3-methylimidazolium tetrafluoroborate [C4mim][BF4] (IL) and paraffin oil (PO) with different percentage of Cp/IL/PO in weight mixing ratios (%w). Voltametric signals of 2,4,6- trinitrotoluene in phosphate buffer solution 0.05 M with pH = 8 on these modified electrodes was recorded. The modified electrode with ratio Cp/IL/PO equal to 80:10:10 is confirmed to be the best in current signal measurement. In term of TNT electrochemical detection with 0.03-22 ppm concentration range, ILPCEs pointed out advantages over conventional glassy carbon electrode by lower detection limit, better performance in signal collecting, more stable and higher reproducible response. Keywords: Trinitrotoluene, carbon paste, ionic liquid, modified electrodes, electrochemical sensors.